ETHNOMATHEMATICS EXPLORATION OF GEOMETRIC TRANSFORMATION CONCEPTS IN TRADITIONAL CLOTHES OF THE DAYAK KENYAH TRIBE - Abbas, Abdul Basir; Muhtadin, Achmad; Jalung, Krismarlina (Ethnomathematics Journal, 2024)
This study aims to explore the traditional clothes of the Dayak Kenyah tribe and is related to the concept of geometric transformation. This type of research is qualitative research with an ethnographic approach. The subject of this research is the traditional clothes and accessories of the Dayak Kenyah tribe, while the object of this study is the geometric transformation concept of the Dayak Kenyah in traditional clothes motifs. Data was collected through observation, interview, and documentation in traditional clothes of the Dayak Kenyah tribe. Based on the exploration results, it was found thirteen traditional clothes and accessories for the Dayak Kenyah traditional clothes (Bluko, Besunung, Tabit, Kelempit, Baheng, Sapai, Ta'a, Tapung, Sabau, Uleng, Seleng, Kirip, and Anting) which are examples of the application geometric transformation concepts. The results of the research show that the motifs found in the traditional clothing of the Dayak Kenyah tribe can be a concrete example of the concept of geometric transformation. The geometric transformation concepts found include (1) Translation in Tabit, Kelempit, Ta'a, and Sabau; (2) Reflections in Bluko, Tabit, Kelempit, Sapai, Ta'a, Tapung, Sabau, Uleng, Seleng and Earrings; (3) Rotation of the Tabit; (4) No dilatation was found in the traditional clothes motifs of the Dayak Kenyah tribe. Apart from that, in Besunung, Baheng, and Kirip, there is no concept of geometric transformation. The example represented in the traditional clothes of the Dayak Kenyah tribe can then become an alternative recommendation for learning media so that students can better interpret geometric transformation material contextually.